Study on the Degradation of Sodium Diethyldithiocarbamate (DDTC) in Artificially Prepared Beneficiation Wastewater with Sodium Hypochlorite - Baoyu Cui; Xuetao Wang; Qiang Zhao; Wengang Liu (Journal of Chemistry)
The degradation of DDTC in beneficiation wastewater has become an increasingly concerned issue due to the serious effects on the environment. In this study, the degradation characteristics of DDTC in artificially prepared beneficiation wastewater were investigated by adding sodium hypochlorite as an oxidant, and the influences of different degradation conditions on removal efficiency of DDTC were analyzed systematically. The results indicated that the degradation rate of DDTC without sodium hypochlorite added can reach 88.4% in a stewing time of 6 h. When the dosage of sodium hypochlorite was 400 mg·L−1, the degradation rate of DDTC can reach 91.28% for 1 min reaction time under the natural condition of pH value 5.98 and reaction temperature 25°C. The DDTC in the wastewater was firstly degraded into carbon disulfide and diethylamine, and then carbon disulfide was further degraded into CO2, S, or SO42−, while diethylamine was degraded into N2 and CO2. The research results can provide a technical basis for the treatment of beneficiation wastewater containing DDTC.